DAMPAK HANCURNYA GEDUNG WTC AMERIKA SERIKAT TERHADAP NILAI TUKAR MATA UANG BEBERAPA NEGARA ASEAN - Utami, Mudji; Suprihhadi, Heru (Department of Management - Faculty of Business and Economics. Universitas Surabaya., 2003)
The falling down of WTC building in US at September 11, 2001 give the seriously impact to the foreign exchange rate fluctuation, especially for the given countries around the world whose has deeply active transaction concern to US Dollar, including the countries in ASEAN region. The change of foreign exchange rate in ASEAN region not always appreciated but some of them turn to depreciated when it's ahead to US Dollar. This situation will influence the discrepancy on rate of return of US dollar in ASEAN countries, before and after the accident of September 11.According to our research, the result significantly explore the differentiation on rate return during seven days before and after the accident but there's no differentiation on rate of return during three days and the day after seven days from the accident.